Effect of the Depth of Cold Water Immersion on Sleep Architecture and Recovery Among Well-Trained Male Endurance Runners - Maxime Chauvineau; Florane Pasquier; Vincent Guyot; Anis Aloulou; Mathieu Nedelec (Frontiers Media S.A., 2021)
Introduction: The aim of the present study was to investigate the effect of the depth of cold water immersion (CWI) (whole-body with head immersed and partial-body CWI) after high-intensity, intermittent running exercise on sleep architecture and recovery kinetics among well-trained runners.Methods: In a randomized, counterbalanced order, 12 well-trained male endurance runners (V.O2max = 66.0 ± 3.9 ml·min−1·kg−1) performed a simulated trail (≈18:00) on a motorized treadmill followed by CWI (13.3 ± 0.2°C) for 10 min: whole-body immersion including the head (WHOLE; n = 12), partial-body immersion up to the iliac crest (PARTIAL; n = 12), and, finally, an out-of-water control condition (CONT; n = 10). Markers of fatigue and muscle damage-maximal voluntary isometric contraction (MVIC), countermovement jump (CMJ), plasma creatine kinase [CK], and subjective ratings-were recorded until 48 h after the simulated trail. After each condition, nocturnal core body temperature (Tcore) was measured, whereas sleep and heart rate variability were assessed using polysomnography.Results: There was a lower Tcore induced by WHOLE than CONT from the end of immersion to 80 min after the start of immersion (p < 0.05). Slow-wave sleep (SWS) proportion was higher (p < 0.05) during the first 180 min of the night in WHOLE compared with PARTIAL. WHOLE and PARTIAL induced a significant (p < 0.05) decrease in arousal for the duration of the night compared with CONT, while only WHOLE decreased limb movements compared with CONT (p < 0.01) for the duration of the night. Heart rate variability analysis showed a significant reduction (p < 0.05) in RMSSD, low frequency (LF), and high frequency (HF) in WHOLE compared with both PARTIAL and CONT during the first sequence of SWS. No differences between conditions were observed for any markers of fatigue and muscle damage (p > 0.05) throughout the 48-h recovery period.Conclusion: WHOLE reduced arousal and limb movement and enhanced SWS proportion during the first part of the night, which may be particularly useful in the athlete's recovery process after exercise. Future studies are, however, required to assess whether such positive sleep outcomes may result in overall recovery optimization.